(untitled) (Indian Journal of Animal Production and Management, 2024)
An experiment was carried out with the objective of studying the performance of Vanaraja birds as influenced by the dietary inclusion of linseed meal by replacing GNC. The study was conducted with 120 female Vanaraja chicks which were randomly divided into four groups designated as T1(control), T2, T3, and T4, and subjected to four dietary levels of linseed meal by replacing GNC at the rate of 0%, 4%, 8%, and 12%, respectively. The birds were reared under deep litter system up to 8 weeks of age and thereafter in cages following standard management practices. Linseed meal had a significant effect on the overall mean body weight, gain in weight, feed intake, and feed conversion efficiency. The overall mean body weight and gain in weight was found to be significantly (p<0.05) higher in T1 followed by T2, T4, and the least in T3. Significantly (p<0.05) lower feed intake, better mean FCR and performance index was observed at4% level of linseed meal as compared to the control group. Mortality was nil in treated groups while it was 3.4 % in control group. Inclusion of linseed meal by replacing GNC had positive effect (p<0.05) on the blood cholesterol, HDL and triglycerides both at 4th and 9th month particularly at 8 % level. On the basis of the above findings, it was concluded that replacement of GNC with linseed meal had positive effect on the performance of Vanaraja birds particularly the blood constituents, which is indicative of its potential health benefits.